The giant of thought. On the 200th anniversary of Hermann Ludwig Ferdinand von Helmholtz - V. V. Neroev; E. N. Orlova; O. V. Khramova (Российский офтальмологический журнал, 2021)
With this article, the Journal is commemorating the 200th anniversary of Hermann von Helmholtz, the genius scientist of the 19th century. The article outlines the main facts of his biography, and discusses the major areas of his activity in a variety of branches of science, testifying the versatility of his talent. Special attention is given to Helmholtz’ contribution into the development of ophthalmology. The importance of his collaboration with prominent researchers of his time, including those descending from Russia, is emphasized.